2001
DOI: 10.1073/pnas.181181198
|View full text |Cite
|
Sign up to set email alerts
|

A phosphatidylinositol 3-kinase/Akt pathway promotes translocation of Mdm2 from the cytoplasm to the nucleus

Abstract: The Mdm2 oncoprotein promotes cell survival and cell cycle progression by inhibiting the p53 tumor suppressor protein. To regulate p53, Mdm2 must gain nuclear entry, and the mechanism that induces this is now identified. Mitogen-induced activation of phosphatidylinositol 3-kinase (PI3-kinase) and its downstream target, the Akt͞PKB serine-threonine kinase, results in phosphorylation of Mdm2 on serine 166 and serine 186. Phosphorylation on these sites is necessary for translocation of Mdm2 from the cytoplasm int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
863
7
16

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,070 publications
(926 citation statements)
references
References 49 publications
(46 reference statements)
40
863
7
16
Order By: Relevance
“…Furthermore, inhibition of HDM2 by antisense oligonucleotides resulted in accumulation of nuclear p53 in neuroblastoma, as well as other tumors with p53 cytoplasmic sequestration (Lu et al, 2000). In addition, phosphorylation of HDM2 at ser166 has been shown to promote HDM2 nuclear localization (Mayo and Donner, 2001;Ashcroft et al, 2002). Thus, the downregulation of HDM2 and P-HDM2 seen in this study is consistent with a role for COX inhibitors in blocking p53 nuclear export in a manner similar to that induced by some DNA damaging agents.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, inhibition of HDM2 by antisense oligonucleotides resulted in accumulation of nuclear p53 in neuroblastoma, as well as other tumors with p53 cytoplasmic sequestration (Lu et al, 2000). In addition, phosphorylation of HDM2 at ser166 has been shown to promote HDM2 nuclear localization (Mayo and Donner, 2001;Ashcroft et al, 2002). Thus, the downregulation of HDM2 and P-HDM2 seen in this study is consistent with a role for COX inhibitors in blocking p53 nuclear export in a manner similar to that induced by some DNA damaging agents.…”
Section: Discussionsupporting
confidence: 85%
“…However, another plausible mechanism that may explain our findings is the downregulation of Akt/PDK1. Mitogeninduced activation of PI3-kinase and its downstream target Akt results in phosphorylation of HDM2 on ser166 and 168 and enhanced HDM2 nuclear localization (Mayo and Donner, 2001;Ashcroft et al, 2002). Interestingly, a number of studies have demonstrated that COX-2 inhibitors induce apoptosis by blocking Akt activation in adult carcinomas (Hsu et al, 2000;Arico et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akt also phosphorylates and translocates Mdm2 from the cytoplasm into the nucleus, resulting in promoting p53 degradation and cell-cycle arrest (Mayo and Donner, 2001). In the cells containing normal p53, suppression of Akt signaling pathway upregulates p53 expression and abrogates cell-cycle progression in this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Rescue of p53-induced apoptosis by survival factors has been associated with the activation of Akt kinase (Sabbatini and McCormick 1999). Akt can phosphorylate and activate MDM2, thereby enhancing the degradation of p53 (Mayo and Donner 2001;Zhou et al 2001). Thus, up-regulation of WT p53 in A549 cells after treatment with either bufalin or inhibitor of PI3 K/ Akt (LY), as observed in our study, could be explained by down-regulation of the pAkt/MDM2 pathway.…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Protein mentioning
confidence: 99%